Webinar Edukatif-Reflektif Sebagai Strategi Penguatan Literasi Digital Etis dan Berkelanjutan untuk Mendukung Sustainable Development Goals (SDGS) - Nur, Delyardi; Febrina Agustin, Reza; Pratama Putra, Yuda (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
The rapid development of digital transformation brings great opportunities as well as serious challenges, especially related to the low level of ethical, inclusive, and sustainable digital literacy. Inequality of access, misuse of technology, and lack of critical public understanding of the digital space are the main problems that need to be overcome through a participatory educational approach. This community service activity aims to improve ethical and sustainable digital literacy. This community service activity is carried out through a cross-campus webinar series program designed to improve the digital literacy of students, young lecturers, and the general public. The method used is an educational-reflective approach that emphasizes active participation, critical dialogue, and the preparation of concrete action plans using the Digital Action Plan Canvas. The results of the activity showed a significant increase in knowledge, critical awareness, and participants' ability to formulate contextual and applicable digital strategies. Pre-test and post-test evaluations showed an increase in the average digital literacy comprehension score, while reflection through action plans strengthened participants' commitment to apply learning into real practice. In addition, this activity succeeded in expanding academic networks across institutions and building strategic collaborations that are oriented towards sustainability. The discussion shows that the educational-reflective webinar model is effective in addressing the digital literacy gap, supports the SDG 4 (quality education) and SDG 17 (global partnership) agendas, and can be replicated in various community contexts. With an adaptive, participatory, and collaborative approach, this activity makes a real contribution to improving ethical and inclusive digital literacy in supporting sustainable development.